Local, systemic and immunologic safety comparison between xenogeneic equine umbilical cord mesenchymal stem cells, allogeneic canine adipose mesenchymal stem cells and placebo: a randomized controlled trial - Punzón, Eva; García-Castillo, María; Rico, Miguel A.; Padilla, Laura; Pradera, Almudena (Frontiers in Veterinary Science, 2023)
Mesenchymal stem cells are multipotent cells with a wide range of therapeutic applications, including, among others, tissue regeneration. This work aims to test the safety of intra-articular administration of equine umbilical cord mesenchymal stem cells in young healthy dogs under field conditions following single and repeated administration. This was compared with the safety profile of allogeneic mesenchymal stem cells and placebo in order to define the safety of xenogeneic use of mesenchymal stem cells when administered intra-articular. 24 police working dogs were randomized in three groups in a proportion 1:1:1. EUC-MSCs and CAD-MSCs were obtained from healthy donors and were manufactured following company SOPs and under GMP and GMP-like conditions respectively and compliant all necessary controls to ensure the quality of the treatment. The safety of the treatment was evaluated locally, systemically and immunologically. For this purpose, an orthopedic examination and Glasgow test for the assessment of pain in the infiltrated joint, blood tests, clinical examination and analysis of the humoral and cellular response to treatment were performed. No adverse events were detected following single and repeated MSC administration despite both equine and canine MSC generate antibody titres in the dogs. The intra-articular administration of equine umbilical cord mesenchymal stem cells in dogs has demonstrated to be safe.